Perio J 2020
DOI: 10.26810/perioj.2020.a2
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Periodontal Diseases – Old is Gold or New is Bold? A Survey Study in Egypt

Abstract: Background: A consensus was reached for a new classification system for periodontal and peri-implant diseases and conditions and was proposed by a group of world experts in 2017. Since then, there have been ongoing debates among periodontists regarding the application of the new classification. This study aims to shed light on the current understanding of the new classification among Egyptian periodontists. Methods: This cross-sectional survey study was performed using an anonymous manually distributed questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…A DP é uma das doenças crônicas mais prevalentes da humanidade, classificando-se em: periodontite necrosante, periodontite e periodontite como manifestação de doenças sistêmicas (37,38). Na sua forma mais grave, a DP pode levar à perda de estruturas ósseas e, consequentemente, à perda dentária, afetando negativamente a saúde do indivíduo (4).…”
Section: Doença Periodontalunclassified
“…A DP é uma das doenças crônicas mais prevalentes da humanidade, classificando-se em: periodontite necrosante, periodontite e periodontite como manifestação de doenças sistêmicas (37,38). Na sua forma mais grave, a DP pode levar à perda de estruturas ósseas e, consequentemente, à perda dentária, afetando negativamente a saúde do indivíduo (4).…”
Section: Doença Periodontalunclassified
“…This new diagnostic classification intends to facilitate documentation of PD diagnoses in general dental practices where most periodontal diseases are diagnosed and managed. However, studies have reported gaps in implementing the 2018 classification in clinical settings 8 10 , which is expected when transitioning to a new diagnostic system. In addition, considerable variations exist among dental practitioners and dental students' use of this system that could lead to under- or over-estimation of PD 6 , 11 .…”
Section: Introductionmentioning
confidence: 99%